“Seeing” and “feeling” architecture: how bodily self-consciousness alters architectonic experience and affects the perception of interiors - Pasqualini, Isabella; Llobera, Joan; Blanke, Olaf (Frontiers in Psychology, 2013)
Over the centuries architectural theory evolved several notions of embodiment, proposing in the 19th and 20th century that architectonic experience is related to physiological responses of the observer. Recent advances in the cognitive neuroscience of embodiment (or bodily self-consciousness) enable empirical studies of architectonic embodiment. Here, we investigated how architecture modulates bodily self-consciousness by adapting a video-based virtual reality setup previously used to investigate visuo-tactile mechanisms of bodily self-consciousness. While standing in two different interiors, participants were filmed from behind and watched their own virtual body online on a head-mounted display. Visuo-tactile strokes were applied in synchronous or asynchronous mode to the participants and their virtual body. Two interiors were simulated in the laboratory by placing the sidewalls either far or near from the participants, generating a large and narrow room. We tested if bodily self-consciousness was differently modulated when participants were exposed to both rooms and whether these changes depend on visuo-tactile stimulation. We measured illusory touch, self-identification and performed length estimations. Our data show that synchronous stroking of the physical and the virtual body induces illusory touch and self-identification with the virtual body, independent of room-size. Moreover, in the narrow room we observed weak feelings of illusory touch with the sidewalls and of approaching walls. These subjective changes were complemented by a stroking-dependent modulation of length estimation only in the narrow room with participants judging the room-size more accurately during conditions of illusory self-identification. We discuss our findings and previous notions of architectonic embodiment in the context of the cognitive neuroscience of bodily self-consciousness and propose an empirical framework grounded in architecture, cognitive neuroscience, and virtual reality.